2019
DOI: 10.1037/pas0000748
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of exposure to trauma and childhood adversities in a clinical sample of youth.

Abstract: Categorizing and quantifying exposure to trauma and childhood adversities (CAs) presents a significant measurement and analytic challenge. The current study examined the co-occurrence of trauma and CA types using network analyses, an alternative to traditional measurement models. The Trauma History Profile, assessing lifetime exposure to 20 different trauma and CA types, was administered to 618 treatment-seeking children and youth ages 4 to 18 years (52.8% female). The generalized similarity model (Kovács, 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…The outbreak of chronic stress induced by childhood trauma is directly related to the emotional processes derived from adverse experiences [9,27]. A traumatic experience can cause anguish and suffering, leading the individual to a state of chronic emotional stress [27][28][29]. The emotional repercussions of trauma can be conscious or unconscious, since the individual perception will depend on the stimulus received from the environment since childhood [30,31].…”
Section: Emotional Processes Resulting From Childhood Traumamentioning
confidence: 99%
“…The outbreak of chronic stress induced by childhood trauma is directly related to the emotional processes derived from adverse experiences [9,27]. A traumatic experience can cause anguish and suffering, leading the individual to a state of chronic emotional stress [27][28][29]. The emotional repercussions of trauma can be conscious or unconscious, since the individual perception will depend on the stimulus received from the environment since childhood [30,31].…”
Section: Emotional Processes Resulting From Childhood Traumamentioning
confidence: 99%
“…While network research in the social and behavioral sciences has often focused on relationships between persons, nodes can be virtually anything (e.g., individuals, organizations, or experiences) [17e19]. Analogous examples are networks of co-occurring psychopathological symptoms (e.g., sleep difficulties, hyperarousal, and memory loss) [19,20], traumatic experiences (e.g., psychological maltreatment, neglect, and domestic violence) [21,22], or criminal activity (e.g., domestic violence and violent offenses) [23]. Prior studies demonstrate that network analyses can reveal a complex system of interrelated symptoms, experiences, and behaviors while highlighting the significance of each to the overall system [21,22].…”
Section: A Network Approachmentioning
confidence: 99%
“…Analogous examples are networks of co-occurring psychopathological symptoms (e.g., sleep difficulties, hyperarousal, and memory loss) [19,20], traumatic experiences (e.g., psychological maltreatment, neglect, and domestic violence) [21,22], or criminal activity (e.g., domestic violence and violent offenses) [23]. Prior studies demonstrate that network analyses can reveal a complex system of interrelated symptoms, experiences, and behaviors while highlighting the significance of each to the overall system [21,22]. From a practical point of view, a network approach can guide early intervention efforts by identifying which nodes may signal the onset of other nodes that they are directly or indirectly connected to.…”
Section: A Network Approachmentioning
confidence: 99%
“…Previous studies have found that psychological maltreatment are related to posttraumatic stress symptoms (e.g. Caston and Frazier, 2013; Gilman et al, 2013; Hodgdon et al, 2019; McIlveen et al, 2019). Thus, viewing from the lens of the theory of capture, we expect that social adversity may overly focus attention on the negative perceptions of an event.…”
mentioning
confidence: 93%